Anathallis transtalamancana Karremans & Chinchilla, sp. nov. - Karremans Lok, Adam Philip (2020)
The new species is similar to A. endresii (Luer) Pridgeon & M.W.Chase, but can be distinguished by the 1-2-flowered raceme (vs. 3-4-flowered), the yellowish (vs. purple), glabrous, 4.6-4.8 mm long sepals (vs. ciliate, 5.5-6.0 mm long), the narrowly lanceolate, acuminate (vs. oblong, acute) petals, the oblong lip, with a pair of small lateral lobes below the middle, and an obtuse, mucronate apex (lip narrowly ovate, without lateral lobes, apex narrow, rounded). Anathallis grayumii (Luer) Luer is also similar but has narrower sepals (1.0-1.25 vs. 1.5-1.9 mm) and petals (0.6 vs. 1.1-1.6 mm), and the lip is dark purple and narrowly oblong to lanceolate (vs. yellowish-orange and oblong).